Performance of Junctional Tourniquets in Normal Human Volunteers. (3rd July 2015) - Kragh, John F.; Kotwal, Russ S.; Cap, Andrew P.; Aden, James K.; Walters, Thomas J.; Kheirabadi, Bijan S.; Gerhardt, Robert T.; DeLorenzo, Robert A.; Pidcoke, Heather F.; Cancio, Leopoldo C.
Abstract Background. Inguinal bleeding is a common and preventable cause of death on the battlefield. Four FDA-cleared junctional tourniquets (Combat Ready Clamp [CRoC], Abdominal Aortic and Junctional Tourniquet [AAJT], Junctional Emergency Treatment Tool [JETT], and SAM Junctional Tourniquet [SJT]) were assessed in a laboratory on volunteers in order to describe differential performance of models. Objective. To examine safety and effectiveness of junctional tourniquets in order to inform the discussions of device selection for possible fielding to military units. Methods. The experiment measured safety and effectiveness parameters over timed, repeated applications. Lower extremity pulses were measured in 10 volunteers before and after junctional tourniquet application aimed at stopping the distal pulse assessed by Doppler auscultation. Safety was determined as the absence of adverse events during the time of application. Results. The CRoC, SJT, and JETT were most effective; their effectiveness did not differ (p > 0.05). All tourniquets were applied safely and successfully in at least one instance each, but pain varied by model. Subjects assessed the CRoC as most tolerable. The CRoC and SJT were the fastest to apply. Users ranked CRoC and SJT equally as performing best. Conclusion. The CRoC and SJT were the best-performing junctional tourniquets using this model.